ACUTE PROMYELOCYTIC LEUKEMIA: AN EXPERIENCE ON 95 GREEK PATIENTS TREATED IN THE ALL-TRANS-RETINOIC ACID ERA - Pagoni, Maria; Garofalaki, Maria; Panitsas, Fotios; Manola, Kalliopi; Psarra, Katerina; Economopoulos, Panagiotis (Mediterranean Journal of Hematology and Infectious Diseases, 2011)
Acute promyelocytic leukemia (APL) is highly curable with the combination of all-trans-retinoic acid (ATRA) and anthracycline based chemotherapy, but the percentage of early deaths remains high. In the present study, we report the clinical, immunophenotypic, cytogenetic and molecular characteristics and outcome of APL patients diagnosed and treated in various Hospitals of Greece and Cyprus. We describe the data of ninety-five APL patients who were diagnosed during the last 15 years. Seven (7.4%) newly diagnosed APL patients died due to intracranial hemorrhage within 72 hours of presentation. All but two patients were induced with ATRA alone or ATRA plus chemotherapy. The early death rate was 14.9%. After induction all 80 evaluable patients achieved complete hematologic remission. The cumulative incidence of relapse was 18.3%. Eight of the ten relapsed patients were successfully salvaged, while both patients with molecularly resistant disease died during salvage treatment. Overall survival (OS) at 5 years was 78.4% and disease free survival (DFS) 73.6%. In multivariate analysis of OS age over 60 years, DIC at diagnosis and marginally major hemorrhage at presentation were identified as adverse prognostic factors. In the subgroup of patients with available data on FLT3 mutation status (49 out of 94), ITD positivity also remained as an independent prognostic factor in the final model of OS, together with major hemorrhage and marginally high Sanz score. We found a close correlation between the CD2 expression and the development of the differentiation syndrome (DS). In conclusion, the main problem in managing patients with APL is still the high early death rate.